2012
DOI: 10.1016/j.ajpath.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Interleukin-6 Receptor Alleviates Disease in Mouse Model of Scleroderma

Abstract: Activation of fibroblasts by interleukin-6 (IL-6) is implicated in the pathogenesis of scleroderma, suggesting that the inhibition of fibroblast activation may be a promising scleroderma treatment. In this study, we used an IL-6 blocking antibody (Ab) and Il-6 knockout (Il-6KO) mice to examine the role of IL-6 in the bleomycin (BLM)-induced mouse model of scleroderma. BLM was administered to C57BL/6 and Il-6KO mice to induce dermal sclerosis. BLM-treated and control phosphate-buffered saline-treated mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 32 publications
(20 reference statements)
8
78
0
3
Order By: Relevance
“…Moreover, lung tissue pathology, on day 21 after bleomycin treatment, showed significant fibrotic changes with increased collagen content in WT mice compared with IL-6 KO mice (p < 0.05) [14]. Kitaba et al obtained similar results with IL-6 KO bleomycin mice having reduced dermal fibrosis comparing with the WT mice [15].…”
Section: B-cell Depletionsupporting
confidence: 64%
“…Moreover, lung tissue pathology, on day 21 after bleomycin treatment, showed significant fibrotic changes with increased collagen content in WT mice compared with IL-6 KO mice (p < 0.05) [14]. Kitaba et al obtained similar results with IL-6 KO bleomycin mice having reduced dermal fibrosis comparing with the WT mice [15].…”
Section: B-cell Depletionsupporting
confidence: 64%
“…24 IL-6 produced from dermal fibroblasts also contribute to fibrosis by activating fibroblasts to myofibroblasts, which are known to produce collagen. 25 In this study, we found that OCT significantly suppressed the expression of not only TGFb-induced POSTN expression, but also IL-4 and IL-13-induced POSTN expression in dermal fibroblasts. As POSTN is an essential matricellular protein in skin sclerosis of SSc patients and in a BLM-induced scleroderma model, 15 we hypothesize that OCT suppresses dermal sclerosis in part by downregulating the expression of POSTN.…”
Section: Discussionmentioning
confidence: 67%
“…Second, IL-6 promotes collagen production and expression of α-smooth muscle actin by dermal fi broblasts, as well as endothelial cell activation and apoptosis in endothelial cell-neutrophil co-cultures. Moreover, in models of SSc induced by bleomycin, IL-6 blockade by administration of anti-IL-6R Ab suppresses myofi broblast activation, resulting in reduced dermal fi brosis [ 58 ]. We observed the benefi cial effects of tocilizumab for two patients with SSc [ 59 ].…”
Section: Effi Cacy Of Tocilizumab In Other Autoimmune Infl Ammatory Dmentioning
confidence: 59%